Src Inhibition Attenuates Liver Fibrosis by Preventing Hepatic Stellate Cell Activation and Decreasing Connective Tissue Growth Factor - Hye-Young Seo; So-Hee Lee; Ji-Ha Lee; Yu Na Kang; Jae Seok Hwang; Keun-Gyu Park; Mi Kyung Kim; Byoung Kuk Jang (Cells, 2020)
The SRC kinase family comprises non-receptor tyrosine kinases that are ubiquitously expressed in all cell types. Although Src is reportedly activated in pulmonary and renal fibrosis, little is known regarding its role in liver fibrosis. This study investigated whether the inhibition of Src protects against liver fibrosis. The expression of Src was upregulated in thioacetamide (TAA)-induced fibrotic mouse liver and cirrhosis of patients, and phospho-Src was upregulated during activation of hepatic stellate cells (HSC). In addition, Src inhibition reduced the expression of α-smooth muscle actin (αSMA) in primary HSCs and suppressed transforming growth factor β (TGF-β)-induced expression of connective tissue growth factor (CTGF) in hepatocytes. Src inhibitor Saracatinib also attenuated TAA-induced expression of type I collagen, αSMA, and CTGF in mouse liver tissues. The antifibrotic effect of Src inhibitors was associated with the downregulation of smad3, but not of signal transducer and activator of transcription 3 (STAT3). In addition, Src inhibition increased autophagy flux and protected against liver fibrosis. These results suggest that Src plays an important role in liver fibrosis and that Src inhibitors could be treat liver fibrosis.